Class Dimension of Social Inequality - O. M. Kuzmuk (Соціологічні студії, 2018)
In this article we look at some of the most influential theories of class, which try to explain class inequality in west and east European societies. Social stratification is considered as a system of social inequality, social differentiation, based on differences in the occupied position and functions performed. Social inequality is the basis of stratification of society and is perceived as its main feature. The theory of social stratification reveals the essence of social inequality in such factors as social status, social role and prestige of functionally describing the social structure.